2020
DOI: 10.1136/jitc-2019-000394
|View full text |Cite
|
Sign up to set email alerts
|

Viral status, immune microenvironment and immunological response to checkpoint inhibitors in hepatocellular carcinoma

Abstract: Background and aimsImmune checkpoint inhibitors (ICIs) targeting the programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) pathway have clinical activity in hepatocellular carcinoma (HCC), but only a subset of patients respond to these therapies, highlighting a need for novel biomarkers to improve clinical benefit. HCC usually occurs in the setting of liver cirrhosis from chronic hepatitis B or C viral infection, but the effects of viral status on the tumor immune microenvironment and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…The antitumor ability of ICIs may depend on other carcinogenetic processes rather than on HBV-related cascades. 31 Ho et al have found that viral etiology has no effect on the tumor immune microenvironment, and viral status should not be adopted as a criterion for ICI medication. 31 Since viral status had no impact on the efficacy of ICIs, it can be inferred that viral load may not compromise the efficacy of anti-PD-1 blockade, which was supported by our data.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor ability of ICIs may depend on other carcinogenetic processes rather than on HBV-related cascades. 31 Ho et al have found that viral etiology has no effect on the tumor immune microenvironment, and viral status should not be adopted as a criterion for ICI medication. 31 Since viral status had no impact on the efficacy of ICIs, it can be inferred that viral load may not compromise the efficacy of anti-PD-1 blockade, which was supported by our data.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma (HCC), PD-1(programmed cell death protein-1)/PD-L1 (programmed death ligand-1) pathways have been inhibited by immune checkpoint inhibitors (ICIs). However, only a small group of GC patients supported these therapeutic techniques, indicating the need for significant biomarkers identification to enhance clinical benefits ( Ho et al, 2020 ). Arresting the communication between PD‐1 protein with its ligands such as PD‐L1, and PD‐L2 may lead to an effective antitumor response and improve clinical outcomes in patients ( Ishikawa et al, 2018 ) (see Fig.…”
Section: Present Day Standard Therapeutics In Gastric Cancermentioning
confidence: 99%
“…The present study provided evidence that baseline HBV DNA load does not affect the tumor response of anti-PD-1 + antiangiogenesis therapy by constructing a retrospective cohort that included HCC patients who received C+A therapy. HBV infection may have no effect on TMEs, as it might integrate into both hepatocytes and tumor cells, and as a result, the anti-tumor ability of anti-PD-1 might not depend on HBV-associated immune attacks but on other carcinogenetic processes (22).…”
Section: Discussionmentioning
confidence: 99%